PENGARUH PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN PAJAK PADA SELF ASSESSMENT SYSTEM DI INDONESIA - Dinar Ayu Adelina; Arif Nugrahanto (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2021)
In the last few decade, the government still faces the problem of low tax revenue. The low level of tax compliance is an issue that is often discussed. In the self-assessment system, the responsibility for fulfilling tax obligations lies in the taxpayer side then the knowledge and comprehension of taxation matter is very substantial. This study aims to identify the relationship between tax knowledge and tax compliance behavior. Furthermore, it also attempts to map the situation of tax knowledge and tax compliance behavior in Indonesian. Through statistical tests with the multiple linear regression method based on a survey involving 260 respondents at a national scale, it is found that knowledge related to tax regulations significantly has influenced tax compliance behavior. Moreover, stepwise regression has identified the two most influential factors, there are knowledge of tax objects and knowledge of tax penalties. In addition, the t-test and MANOVA test prove that the ownership of NPWP, education level, occupation, and income significantly influence the tax knowledge.